Oral health, dental care and mouthwash associated with upper aerodigestive tract cancer risk in Europe: the ARCAGE study - Ahrens, Wolfgang; Pohlabeln, Hermann; Foraita, Ronja; Nelis, Mari; Lagiou, Pagona; Lagiou, Areti; Bouchardy, Christine; Slamova, Alena; Schejbalova, Miriam; Merletti, Franco; Richiardi, Lorenzo; Kjaerheim, Kristina; et al. (Oral oncology, 2014)
OBJECTIVE: We aimed to assess the association of oral health (OH), dental care (DC) and mouthwash with upper-aerodigestive tract (UADT) cancer risk, and to examine the extent that enzymes involved in the metabolism of alcohol modify the effect of mouthwash. MATERIALS AND METHODS: The study included 1963 patients with incident cancer of the oral cavity, oropharynx, hypopharynx, larynx or esophagus and 1993 controls. Subjects were interviewed about their oral health and dental care behaviors (which were converted to scores of OH and DC respectively), as well as smoking, alcohol drinking, diet, occupations, medical conditions and socio-economic status. Blood samples were taken for genetic analyses. Mouthwash use was analyzed in relation to the presence of polymorphisms of alcohol-metabolizing genes known to be associated with UADT. Adjusted odds ratios (ORs) and 95%-confidence intervals [CI] were estimated with multiple logistic regression models adjusting for multiple confounders. RESULTS: Fully adjusted ORs of low versus high scores of DC and OH were 2.36[CI=1.51-3.67] and 2.22[CI=1.45-3.41], respectively, for all UADT sites combined. The OR for frequent use of mouthwash use (3 or more times/day) was 3.23[CI=1.68-6.19]. The OR for the rare variant ADH7 (coding for fast ethanol metabolism) was lower in mouthwash-users (OR=0.53[CI=0.35-0.81]) as compared to never-users (OR=0.97[CI=0.73-1.29]) indicating effect modification (pheterogeneity=0.065) while no relevant differences were observed between users and non-users for the variant alleles of ADH1B, ADH1C or ALDH2. CONCLUSIONS: Poor OH and DC seem to be independent risk factors for UADT because corresponding risk estimates remain substantially elevated after detailed adjustment for multiple confounders. Whether mouthwash use may entail some risk through the alcohol content in most formulations on the market remains to be fully clarified.
Keywords: Alcohol Drinking; studie případů a kontrol; pití alkoholu; Humans; nádory hlavy a krku; Europe; kouření; Genetic polymorphisms; ústní vody; Smoking; Risk Factors; nádory jícnu; orální zdraví; Oral Hygiene; Evropa; rizikové faktory; Esophageal Neoplasms; Mouthwashes; Head and neck neoplasms; Oral Health; lidé; orální hygiena; Case-Control Studies; Head and Neck Neoplasms; Oral hygiene; Oral health